Perimenopause vasomotor symptoms, coronary atherosclerosis and risk of myocardial infarction during menopause: the cardiologist’s perspective - Savonitto, Stefano; Ferri, Luca A.; Colombo, Delia (Menopause Review/Przegląd Menopauzalny, 2018)
Myocardial infarction (MI) is rare in pre-menopausal women, and in most cases has a gender-specific pathogenesis. After menopause, MI incidence increases gradually to equalize men’s rate in the eighth decade of age, with similar pathogenesis. This epidemiological observation has raised a number of hypotheses on the protective effect of estrogen against atherosclerosis and its related diseases. However, MI has a multifactorial pathogenesis with variable contributions of inflammation, eroded or ruptured atherosclerotic plaques, vasoconstriction and thrombosis. Whether perimenopausal vasomotor symptoms are associated with a better, worse or neutral effect on the risk of myocardial infarction has long been disputed. The recent finding of the LADIES ACS study that women reporting transitional vasomotor symptoms have earlier onset myocardial infarction, as compared to women without symptoms, despite similar risk factors and extent of coronary angiographic disease, supports the hypothesis that endothelial dysfunction, or other vasoconstrictive mechanisms, may play a key role in precipitating an acute coronary syndrome at an earlier age. These factors, rather than other atherosclerotic markers, should be specifically investigated in order to elucidate the so far elusive link between vasomotor symptoms and risk of MI.